Karakterisasi pengecoran connecting rod dengan penambahan unsur paduan titanium-boron (Ti-B) - Andika Wisnujati; Muhammad Abdus Shomad; Mudjijana Mudjijana (TURBO [Tulisan Riset Berbasis Online], 2022)
Nowdays, motorcycles become a primary need for people, especially in Indonesia. This has resulted in the increasing number of motorcycle spare parts waste. The waste is in the form of motorcycle components such as wheels, tires, drums, canvas, gear, chains and pistons and many others. Until now, the community has not used this waste, especially the use of used pistons as raw material for casting connecting rods. Connecting rod itself is a motorcycle component made of aluminum. In this study, the authors wanted to analyze the physical and mechanical properties of the casting (imitation) connecting rods made from used pistons with the addition of Titanium Boron (Ti-B) elements. The characterization of the casting results was analyzed by observing the microstructure and Vickers hardness test. The results showed that the physical properties of the foundry material contained 81.6% aluminum and 13.09% silicon, while on microstructure observations with a magnification of 100x, the Al phase and Al-Si alloys were more dominant. In the Vickers hardness test, the hardness result was 79.59 VHN. This is due to the addition of Ti-B elements which can refine grains and reduce porosity in aluminum silicon (Al-Si) alloys for motorcycle connecting rod spare parts.